Integral equation theory for nematic fluids - Holovko, M.F. (Condensed Matter Physics, 2010)
The traditional formalism in liquid state theory based on the calculation of the pair distribution function is generalized and reviewed for nematic fluids. The considered approach is based on the solution of orientationally inhomogeneous Ornstein-Zernike equation in combination with the Triezenberg-Zwanzig-Lovett-Mou-Buff-Wertheim equation. It is shown that such an approach correctly describes the behavior of correlation functions of anisotropic fluids connected with the presence of Goldstone modes in the ordered phase in the zero- eld limit. We focus on the discussions of analytical results obtained in collaboration with T.G. Sokolovska in the framework of the mean spherical approximation for Maier-Saupe nematogenic model. The phase behavior of this model is presented. It is found that in the nematic state the harmonics of the pair distribution function connected with the correlations of the director transverse fluctuations become long-range in the zero- eld limit. It is shown that such a behavior of distribution function of nematic fluid leads to dipole-like and quadrupole-like long-range asymptotes for effective interaction between colloids solved in nematic fluids, predicted before by phenomenological theories. Традиційний формалізм у теорії рідин, що базується на розрахунку парної функції розподілу, узагальнено на нематичні плини. Розглянутий підхід базується на розв'язку орієнтаційно-неоднорідного рівняння Орнштейна - Церніке в поєднанні з рівнянням Трайцінберга - Цванціга - Ловета - Моу - Бафа - Вертгайма. Показано, що даний підхід коректно описує поведінку кореляційних функцій анізотропних флюїдів, обумовлену наявністю голдстоунівських мод у впорядкованій фазі за відсутності впорядковуючого зовнішнього поля. Розглянуто аналітичні результати, одержані у співпраці з Т. Г. Соколовською в межах середньо-сферичного наближення для нематогенної моделі Майєра - Заупе. Представлено фазову діаграму цієї моделі. Встановлено, що в нематичному стані гармоніки парної кореляційної функції, пов'язані з кореляціями флуктуацій поперечних до напрямку директора, стають далекосяжними за відсутності впорядковуючого поля. Показано, що така поведінка функції розподілу нематичного флюїду призводить до дипольно- та квадрупольно-подібних далекосяжних асимптотик ефективної міжколоїдної взаємодії в нематичних флюїдах, передбаченої раніше феноменологічними теоріями.